A holstein cow–calf model for the transfer of ciprofloxacin through milk after a long‐term intravenous infusion. Issue 5 (3rd October 2012) - Chiesa, O. A.; Idowu, O. R.; Heller, D.; Smith, M.; Nochetto, C.; Chamberlain, P. L.; Gehring, R.; von Bredow, J.
Abstract : This study is part of an ongoing effort to develop animal models that provide milk and sufficient infant (offspring) plasma samples to fully describe a drug's pharmacokinetics to quantitate the risk to the nursing infant. Ciprofloxacin was administered to six healthy Holstein cows as a constant rate intravenous infusion (flow rate was weight adjusted) to achieve a steady‐state concentration of approximately 300 ng/mL for 7 days. Plasma and milk samples were collected from the cow at regular intervals over the course of the 7 days. The plasma and milk samples were analyzed for ciprofloxacin by high‐performance liquid chromatography. The milk was fed to calves, and calf plasma samples were analyzed to study the lactational transfer of ciprofloxacin from dam to nursing neonate. Remarkably, concentrations of ciprofloxacin in milk were 45 times higher than plasma drug concentrations in the dam. Approximately 6% of the administered dose was transferred to the milk, resulting in an average oral dose of 0.5 mg/kg to the calves with every feeding. The drug did not accumulate in the calves, and plasma concentrations were between one‐tenth and one‐fifth the plasma concentrations of the dam.